Density operators and other tools of quantum statistics - Ebeling, Werner; Pöschel, Thorsten (Lectures on Quantum Statistics, 2019)
In this chapter, we will introduce useful tools of Quantum Statistics. Most of them will be used in later chapters of this book to solve concrete problems. Our survey covers, of course, the most prominent methods such as density operators introduced by von Neumann and Landau, Wigner’s phase-space functions method, and Bogolyubov’s method of reduced density operators. Matsubara’s thermodynamical Green’s functions and real-time Green’s functions are important methods in the field of quantum plasmas but are discussed here only rather briefly.
CRIS-Team Scopus Importer:2019-05-28